HUBUNGAN PARITAS DAN PENDIDIKAN DENGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DI PUSKESMAS TULUNG SELAPAN TAHUN 2020 - Heryanti; Clara Sintia Mahesa (Jurnal Kesehatan dan Pembangunan, 2022)
Pregnancy involves psychological changes or physiologic from mother and social changes in family. Pregnancy alert is syndrome which indicates that mother and baby are in dange. The aims of this research is to find out the correlation parity and mother’s education with pregnant mother’s knowledgeabout pregnancy alert in Tulung Selapan Health Care year 2020. This research used analytic survey method. This research population is all maternities TM III who come to Tulung Selapan Health Care in December 2020. Sample taking of this research is acedental sampling method. Sample of this research is 37 respondents. From the result of univariate analysis obtained well - knowledge respondent (73,0%) more than enough - knowledge motherand lack namely each one (13,5%). Mother’s parity and high parity (70,3%) more thanwith mother’slow parity (29,7%). Mother with high education (67,6%) more than with mother with low education (32,4%). From the result of bivariate analysis reached that there is correlation between parity with maternity’s knowledge about pregnancy alert in Hj. Zuniawaty Apprentice Palembang year 2020 ( There is correlation between mother with pregnant mother’s knowledge about pregnancy alert in Tulung Selapan Health Care year 2020 ( Suggestion from researcher that this research result can be as evaluation subtance for Tulung Selapan Health Care so that can increase antenatal care service, can enhance attention to people mainly to maternity in giving service according to prenatal care.